Best practice in audiology: context matters - Hlayisi, Vera-Genevey; Ramkumar, Vidya; Petersen, Lucretia; Vangerwua, Barnabas (Frontiers in Audiology and Otology, 2024)
Historically, modern audiology evolved from the United States of America (USA) after the Second World War, where hearing rehabilitation programs were established across the country. Since then, audiology practice and the profession as a whole has expanded from the west to the far east and global south with considerable contextual variations. Thus, the purpose of this paper is to increase conversation and engagement on definitions and the drawbacks of a single lens approach to the use of best practice guidelines in Audiology. It is important to develop a more expansive lens as influenced by different contexts such as Africa, Asia, and South America that will in turn help facilitate a multidimensional approach to audiology practice and what is considered “best practice.”